FORMULATION AND OPTIMIZATION OF NIFEDIPINE LOADED NANOCARRIERS - JADHAV, ASHWINI; VARGHESE CHERIYAN, BINOY (International Journal of Applied Pharmaceutics, 2021)
Objective: The main aim of this study to formulate a nifedipine-loaded nanocarrier for improving solubility and bioavailability. Methods: To improve the solubility of drug, nifedipine-loaded nanocarrier (lipotomes) were prepared by using the film lipid hydration technique. lipotomes were prepared by using tween 80, which is used for increasing solubility and cetyl alcohol for lipophilic environment. Drug excipients interaction determined by FTIR. lipotomes were characterized for particle size, Entrapment efficiency and zeta potential. lipotomes were optimized by using Design-Expert 12 software. Optimized formula further lyophilized by using different cyroproyectant to improve the stability and oral administration of the drug. Results: FTIR shows there was no interaction between formulation ingredients. Mean particle size, entrapment efficiency, zeta potential was determined and found to be 308.1 nm, 96.7%, 20.1mV, respectively. Surface morphology of lipotomes was observed by a scanning electron microscope (SEM). Optimized lipotomes was lyophilized with Mannitol (8% w/v) was the ideal cryoprotectant to retain the physicochemical characteristics of the OLT formulation after lyophilization. Conclusion: Nifedipine loaded nanocarrier was successfully prepared, using film hydration method. Which have good particle size, EE% and zeta potential. After lyophilization no significant changes was observed in particle size with good physical stability, so it could be a good choice for conventional drug delivery system by doing further investigation as in vitro and in vivo study